Leishmania naiffi and Leishmania guyanensis reference genomes highlight genome structure and gene evolution in the Viannia subgenus. Issue 4 (25th April 2018) - Coughlan, Simone; Taylor, Ali Shirley; Feane, Eoghan; Sanders, Mandy; Schonian, Gabriele; Cotton, James A.; Downing, Tim
Abstract : The unicellular protozoan parasite Leishmania causes the neglected tropical disease leishmaniasis, affecting 12 million people in 98 countries. In South America, where the Viannia subgenus predominates, so far only L. ( Viannia ) braziliensis and L. ( V. ) panamensis have been sequenced, assembled and annotated as reference genomes. Addressing this deficit in molecular information can inform species typing, epidemiological monitoring and clinical treatment. Here, L. ( V. ) naiffi and L. ( V. ) guyanensis genomic DNA was sequenced to assemble these two genomes as draft references from short sequence reads. The methods used were tested using short sequence reads for L. braziliensis M2904 against its published reference as a comparison. This assembly and annotation pipeline identified 70 additional genes not annotated on the original M2904 reference. Phylogenetic and evolutionary comparisons of L. guyanensis and L. naiffi with 10 other Viannia genomes revealed four traits common to all Viannia : aneuploidy, 22 orthologous groups of genes absent in other Leishmania subgenera, elevated TATE transposon copies and a high NADH-dependent fumarate reductase gene copy number. Within the Viannia, there were limited structural changes in genome architecture specific to individual species: a 45 Kb amplification on chromosome 34 was present in all bar L. lainsoni, L. naiffi had a higher copy number of the virulence factor leishmanolysin, and laboratory isolate L. shawi M8408 had a possible minichromosome derived from the 3' end of chromosome 34 . This combination of genome assembly, phylogenetics and comparative analysis across an extended panel of diverse Viannia has uncovered new insights into the origin and evolution of this subgenus and can help improve diagnostics for leishmaniasis surveillance.